Performance and opportunity of motor stimulation in infants with and without microcephaly: Case-control study (Research, Society and Development, 2021)
The study aimed to characterize the gross motor performance and motor stimulation opportunities present in the home environment of infants with microcephaly by Zika virus (ZIKV), comparing them with infants without microcephaly from public health institutions in Northeast Brazil, and to verify the impact of microcephaly and associated factors on the outcomes assessed. Case-control study that used infants' birth, gestational, and maternal sociodemographic data, and the tests: Gross Motor Function Measure (GMFM), Affordances in the Home Environment for Motor Development (AHEMD), and Gross Motor Function Classification System (GMFCS). Multiple linear regression was used to analyze the impact of microcephaly on tests associated with sociodemographic or clinical factors. Forty infants with microcephaly due to ZIKV, mean age 15.3 (3.1) months, and 40 infants without involvement, mean age 14.8 (4.4) months participated. 85% of the infants with microcephaly due to ZIKV classified in level V of the GMFCS. Significant differences (p